Globalization and children’s diets: The case of Maya of Mexico and Central America - Bogin, Barry; Azcorra, Hugo; Wilson, Hannah J.; Vázquez-Vázquez, Adriana; Avila-Escalante, María Luisa; Varela-Silva, Inês; Dickinson, Federico; Castillo-Burguete, Maria Teresa (Anthropological Review, 2014)
Globalization is, in part, an economic force to bring about a closer integration of national economies. Globalization is also a biological, social and ideological process of change. Globalization results in powerful multinational corporations imposing their products on new markets. Food globalization brings about nutritional transitions, the most common being a shift from a locally-grown diet with minimally refined foods, to the modern diet of highly processed foods, high in saturated fat, animal products and sugar, and low in fiber. This paper will examine the influences of food globalization using the Maya of Mexico as a case study. The Maya people of Mexico are a poignant case. Maya health and culture has deteriorated as a result, with highly processed foods affecting physical growth and health of Maya children and their families. The case of the Maya is not isolated and we must come to terms with food globalization if we are to translate research into better child health and well-being.